Model of route programming optimization for a Peruvian logistics company using tools FSMVRPTW - Reyes Morales, Norman (2016)
Activities transport routes logistics companies in Peru are of special relevance in the services they provide. The company currently uses the SAP Business One ERP technology platform v9.1 and support their operations especially the processes of the value chain. Within these processes is the process of delivery which is responsible among other activities to perform scheduling transport routes for deliveries of customer orders throughout the country and especially in Metropolitan Lima; in the latter which has a high complexity attention to orders by the various restrictions to comply and not have a proper tool such activity leaving the decision Programmer routes according to their experience. With tools like FSMVRPTW (Fleet Size and Mix Vehicle Routing Problem with Time Windows) it was possible to find significant savings using a knowledge base, tools and operations research